Editorials - Ivan Čuk (University of Ljubljana Press (Založba Univerze v Ljubljani), 2022)
Dear friends, We hoped COVID-19 would leave us without any serious consequences; however, ScholarOne, the manager of the editorial program we used for many years, has increased their prices so much that we can no longer afford them. In an effort to find a more cost-effective solution, we moved to a new open-source editorial software that is managed by the Ljubljana University. This move required a huge amount of work and means a NEW ADDRESS as well as some delays on the way. We apologise for any inconvenience and hope to get everything running smoothly again by the end of the year.  Our journal can now be found at this new address:   https://journals.uni-lj.si/sgj   The first article - a case study from Brazil - is about an Olympic champion on rings and his preparation strategy to achieve his goals. Very interesting reading! Even though it provides no   scientific evidence to explain why he won at the OG, we decided to publish the article. In our view, such outstanding results are closely related to athlete's personal characteristics and abilities which are difficult to quantify. What we also want to emphasise with this article is planning. Many coaches work without proper planning, whereas here we have an example of good planing. Once we have more knowledge about how gymnasts won their titles, meta analyses will probably help us determine the data that define success. Let us just say this is the first step on this path. Other contributing authors in this issue come from Germany, Serbia, Poland, Slovakia, China, USA, South Korea, Spain and Greece. Again, many different aspects of gymnastics are presented. There are also new challenges for  researchers. In the middle of October, Flavio Bessi organised  International Freiburg Gymnastics Congress online. You can find it at https://www.sport.uni-freiburg.de/en/events/international-gymnastics-congress. Anton Gajdoš drafted the 24rd short historical note introducing Aljaž Pegan from Slovenia. Just to remind you, if you cite the journal, its abbreviation in the Web of Knowledge is SCI GYMN J.  I wish you enjoyable reading and many new ideas for research projects and articles.   Editor-in-Chief